Physical experimental simulation of unconventional reservoir formation process for carboniferous in Hudson Oilfield, Tarim Basin - Rujun Wang; Yongliang Tang; Wei Zhou; Daiyu Zhou; Zangyuan Wu; Guangqiang Shao (Journal of Petroleum Exploration and Production Technology, 2025)
Abstract This study conducts a comprehensive investigation into theformation mechanisms of unconventional oil reservoirs within the Carboniferous strata of the Hudson Oilfield in the Tarim Basin. By combining extensive geological surveys with a custom-built, physically simulated cross-sectional model, this work elucidates the intricate interlayer distribution and its profound impact on reservoir heterogeneity. The non-equilibrium dynamics at the oil–water interface are revealed, shedding light on how variations in reservoir properties influence hydrocarbon migration and accumulation patterns. Through a detailed examination of the interplay among Carboniferous stratigraphy, reservoir instability, and trap adjustments, the findings yield several key outcomes: a demonstrated correlation between randomly distributed calcareous interlayers and resulting in a 30% increase in heterogeneity indices over conventional models. Documentation of oil–water interface inclinations exceeding 100 m and lateral hydrocarbon reversals in 20% of examined reservoirs, contradicting conventional understanding. Evidence that porosity and permeability fluctuations significantly affect hydrocarbon accumulations, leading to a 45% discrepancy in recoverable reserve estimates. And the application of advanced simulations, enhancing unconventional reservoir prediction accuracy by 25% compared to standard geological techniques. These collective insights significantly advance the understanding of Carboniferous unconventional reservoir evolution, informing future exploration strategies and challenging established theories in petroleum geoscience. This highlights the necessity of accounting for reservoir instability and interlayer intricacy in deciphering unconventional hydrocarbon systems.